2015
DOI: 10.1007/s10483-015-1905-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-synchronization theory of dual motor driven vibration system with two-stage vibration isolation frame

Abstract: This paper studies self-synchronization and stability of a dual-motor driven vibration system with a two-stage vibration isolation frame. Oscillation amplitude of the material box large enough can be ensured on the vibration system in order to screen materials. Reduction of the dynamic load transmitted to the foundation can also be achieved for the vibration system. A Lagrange equation is used to set up the motion differential equations of the system, and a dimensionless coupled equation of the eccentric rotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…e coupling items (α 1 , α 2 , Δα 1 , and Δα 2 ) in equations (1) and (2) are symmetrically distributed in the dynamic formula, and according to the equations (13) and (14), the microangular velocity solution indicate that the minor variation of rotational motion in the two rotating systems is mutually limited. e absolute value of synchronous index D, which is smaller than 1, can indicate the synchronous level for the strength of the vibration of machine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e coupling items (α 1 , α 2 , Δα 1 , and Δα 2 ) in equations (1) and (2) are symmetrically distributed in the dynamic formula, and according to the equations (13) and (14), the microangular velocity solution indicate that the minor variation of rotational motion in the two rotating systems is mutually limited. e absolute value of synchronous index D, which is smaller than 1, can indicate the synchronous level for the strength of the vibration of machine.…”
Section: Discussionmentioning
confidence: 99%
“…How to achieve synchronous motion of hydraulic motors has been restricting the application of self-synchronization of hydraulic motor in vibration engineering. But, there are more factors affecting the self-synchronization of hydraulic motors than electric motors [11][12][13], which is determined by the characteristics of the hydraulic system itself, such as flow leakage, large damping, and so on. Our research mainly includes two parts: coupling and compensation.…”
Section: Description Of the Two Rotating Systems In Dynamic Equilibrimentioning
confidence: 99%
See 1 more Smart Citation
“…18 Whether the dual-motor-driven elliptical vibrating screen can reach synchronization or not depends upon the adjustment capability of the capture torque. In other words, the system should meet a synchronization condition for capture torque, 19 as shown below. where Tc is the capture torque; ΔMg is the difference of the driving torque of the two motors; ΔMf is the difference of the friction torque of the two motors.…”
Section: Stable Synchronization Model Of Dual-motor-driven Vibrating mentioning
confidence: 99%
“…A simple way to model this type of isolator is to combine lateral linear springs with a linear (vertical) spring orthogonal to the lateral springs [2-5], resulting in an isolator that has high-static-low-dynamic-stiffness (HSLDS), and many studies have shown there are many ways to achieve this characteristic [1, [6][7][8][9][10][11]. Recently, this concept has been further developed as a two-stage isolator [12][13][14]. In all these cases, the damping was due to a linear viscous damper in parallel with the vertical springs.…”
Section: Introductionmentioning
confidence: 99%